Tobacco prevention and control interventions in humanitarian settings: a scoping review protocol - Muralidhar M Kulkarni; Sanjay Zodpey; Nachiket Gudi; Ansuman Swain; Sanjay Pattanshetty (BMJ Open)
Introduction Tobacco has been a complex global problem that has adversely affected almost all the sectors of society. However, the ill-effects are often most reflected in humanitarian settings, which inadvertently are surmounted by fragile systems. We aim to map tobacco prevention and control intervention in humanitarian settings.Methods and analysis This scoping review will follow the guidelines of the Joanna Briggs Institute. A comprehensive search strategy was designed using Medical Subject Heading terms, subject experts and pertinent reviews. The search was conducted on Medline (through PubMed and Ovid), EMBASE (through OVID), ProQuest Health and Medical Complete, EBSCO (through CINAHL Complete), Scopus and Web of Science databases. Two reviewers will independently screen the identified studies on removing duplicates, which shall be followed by data extraction using a pretested data extraction form. A narrative synthesis approach will be employed to collate the findings from the studies and tabular formats would be used to aid the representation.Ethics and dissemination This review will identify, map and synthesise the interventions for tobacco prevention and control in the humanitarian settings. An ethics committee approval was not sought for this body of work as it does not include human subjects. Results from the study will be disseminated through conference presentations and peer-reviewed publications.